Governing climate change: The impact of board attributes on climate change disclosure - Ooi S.K.; Amran A.; Yeap J.A.L.; Jaaffar A.H. (Inderscience Publishers, 2023)
Industrial management; Board attributes; Corporate governance; Malaysia; Resource dependences; Strategic corporate social responsibilities; Climate change